Endocrinology of the Aging Prostate: Current Concepts - Cannarella, Rossella; Condorelli, Rosita A.; Barbagallo, Federica; La Vignera, Sandro; Calogero, Aldo E. (Frontiers in Endocrinology, 2021)
Benign prostate hyperplasia (BPH), one of the most common diseases in older men, adversely affects quality-of-life due to the presence of low urinary tract symptoms (LUTS). Numerous data support the presence of an association between BPH-related LUTS (BPH-LUTS) and metabolic syndrome (MetS). Whether hormonal changes occurring in MetS play a role in the pathogenesis of BPH-LUTS is a debated issue. Therefore, this article aimed to systematically review the impact of hormonal changes that occur during aging on the prostate, including the role of sex hormones, insulin-like growth factor 1, thyroid hormones and insulin. The possible explanatory mechanisms of the association between BPH-LUTS and MetS are also discussed. In particular, the presence of a male polycystic ovarian syndrome (PCOS)-equivalent may represent a possible hypothesis to support this link. Male PCOS-equivalent has been defined as an endocrine syndrome with a metabolic background, which predisposes to the development of type II diabetes mellitus, cardiovascular diseases, prostate cancer, BPH and prostatitis in old age. Its early identification would help prevent the onset of these long-term complications.